2002
DOI: 10.17221/5805-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Serological survey of the wild boar (Sus scrofa) for tularaemia and brucellosis in South Moravia, Czech Republic

Abstract: Sera of 204 wild boars (Sus scrofa), shot by hunters in the South-Moravian district of Břeclav during 1993-2001, were tested by microagglutination reaction using safranin-stained antigens of Francisella tularensis and Brucella abortus: 10.8% and 8.7% seroreactors, respectively, were detected. The highest (17%) prevalence of tularaemia antibodies was found in wild boars during 1993-1994 at the beginning of a widespread outbreak of tularaemia in South Moravia that started in 1994, a nonsignificantly lower (13%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…However these species are not considered to be particularly susceptible to developing disease. Their potential role as asymptomatic carriers, shedding and/or spreading the infection in nature, has not been investigated [1,7,9,89,90].…”
Section: Sources Of Infection and Routes Of Disseminationmentioning
confidence: 99%
“…However these species are not considered to be particularly susceptible to developing disease. Their potential role as asymptomatic carriers, shedding and/or spreading the infection in nature, has not been investigated [1,7,9,89,90].…”
Section: Sources Of Infection and Routes Of Disseminationmentioning
confidence: 99%
“…B. suis biovar 2 was demonstrated in wild boar in the countries of Central Europe. Kormendy and Nagy (1982) reported on the findings of B. suis biovar 2 in Hungary, Hubalek et al (2002) in Czech Republic, Brglez and Batis (1981) in Slovenia. Godfroid et al (1994) reported on the findings of B. suis biovar 2 in wild boar in Belgium, where it was isolated from 13 (9.2%) out of 141 analysed samples of wild boar.…”
mentioning
confidence: 99%
“…In France Garin-Bastuji et al (2000) also isolated B. suis biovar 2 in about 10% of the analysed materials (spleen) of wild boar. In Central and Western Europe the most o�en causal agent of brucellosis in pigs is B. suis biovar 2 whose natural carriers are hares (Lepus capensis) (Brglez and Batis, 1981;Szulowski et al, 1999) and wild boar (Quinn et al, 1994;GarinBastuji et al, 2000;Hubalek et al, 2002). Brucellosis was diagnosed in different countries and continents by serological examination too.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the la�er case tularemia can be brought to such a diseasefree territory either by transfer of animals when re-populating the area or by the migrating reservoir host -the wild boar (Sus scrofa). As far as the wild boar is concerned, Hubalek et al (2002) found up to 17% of seroprevalence for tularemia and the home range of this species is much larger (about 35 km 2 ; Saunders and Kay, 1996) than in other reservoir hosts of tularemia. The wild boar is a species preferring riverine woodlands (Choquenot and Ruscoe, 2003) and as natural foci of tularemia are most frequent in alluvial areas (Pikula et al, 2003), the wild boar could be the species responsible for the spread of tularemia to new areas.…”
Section: Discussionmentioning
confidence: 93%